STRATEGI PERANCANGAN LAPORAN KEUANGAN PADA UMKM (STUDY KASUS BURGER SIKELING) - Hayati , Fitri; Siregar, Dedy Rahman (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
Micro, small and medium enterprises (MSMEs) play a vital role in the Indonesian economy because they are labor-intensive and use simple technology. The government supports MSME business owners, but they also need administrative and financial management skills to succeed. These capacities are essential to addressing obstacles and increasing MSME success as well as combating poverty and unemployment.